Analysis of Hospital Efficiency and Implications for Financial Performance - Yani Anjani; Tetet Fitrijanti; Resi Ariyasa Qadri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Effective financial performance can have a positive impact on hospital efficiency. When hospitals have good financial performance, they are able to optimize resource management, increase revenue, and reduce operating costs. The objective of this study is to analyze Dr. Kariadi Hospital's efficiency from 2018 to 2022 using a financial ratio analysis approach based on PER-24 of 2018 and examine its implications for financial performance. This study employs secondary data in the form of financial statement data from RSUP Dr. Kariadi Semarang, spanning from 2018 to 2022. The data was evaluated by computing eight financial performance metrics. The results suggest that RSUP is efficient based on several indicators, including the current ratio, collection period, fixed asset turnover, and POBO ratio. While inventory turnover is a good indicator, the return on assets (ROA) is only moderate. However, the cash ratio and return on equity (ROE) still need improvement. As a strategic measure, it is recommended to focus on improving the cash ratio and return on equity (ROE) indicators in order to enhance the efficiency and financial performance of Dr. Kariadi Hospital Semarang in the upcoming period.